ANALISIS PERBANDINGAN METODE RAD DENGAN EXTREME PROGRAMMING UNTUK APLIKASI MANAGEMENT BISNIS UMKM - Ersaputra, Muh Arsyal Afifan; Putri, Anggia Dasa (LPPM Universitas Putera Batam, 2024)
Developing business management applications for micro, small and medium enterprises (MSMEs) is becoming increasingly important in the ever-changing digital age. A project's success is greatly enhanced by the appropriate software development method. The purpose of this research is to compare RAD and XP methods for MSME business management applications. A thorough examination of the concepts of both RAD and XP helps to understand the significant differences between the two methods. In contrast to RAD, which emphasizes rapid development with short iterations, XP prioritized a team approach that involves continuous testing, flexibility, and agile planning. This research guides software developers and MSME business owners in selecting the appropriate methodology for developing business management applications. By comprehending the distinctions, advantages, and challenges of each approach more thoroughly, it is anticipated to achieve efficiency and success in developing business management applications for MSMEs.